Should UK membership exams be held overseas? Yes. (28th July 2011) - Muir, Graeme; Thacker, Justin
Abstract : Graeme Muir and Justin Thacker believe that UK professional qualifications can help other countries improve training and standards, but Delan Devakumar and Kate Mandeville (doi:10.1136/bmj.d4560 ) argue that they lack local relevance